Preeclampsia and syncytiotrophoblast membrane extracellular vesicles (STB-EVs) - Awoyemi, T; Cerdeira, AS; Zhang, W; Jiang, S; Rahbar, M; Logenthiran, P; Redman, C; Vatish, M (Portland Press, 2022)
Preeclampsia (PE) is a hypertensive complication of pregnancy that affects 2–8% of women worldwide and is one of the leading causes of maternal deaths and premature birth. PE can occur early in pregnancy (<34 weeks gestation) or late in pregnancy (>34 weeks gestation). Whilst the placenta is clearly implicated in early onset PE (EOPE), late onset PE (LOPE) is less clear with some believing the disease is entirely maternal whilst others believe that there is an interplay between maternal systems and the placenta. In both types of PE, the syncytiotrophoblast (STB), the layer of the placenta in direct contact with maternal blood, is stressed. In EOPE, the STB is oxidatively stressed in early pregnancy (leading to PE later in gestation- the two-stage model) whilst in LOPE the STB is stressed because of villous overcrowding and senescence later in pregnancy. It is this stress that perturbs maternal systems leading to the clinical manifestations of PE. Whilst some of the molecular species driving this stress have been identified, none completely explain the multisystem nature of PE. Syncytiotrophoblast membrane vesicles (STB-EVs) are a potential contributor to this multisystem disorder. STB-EVs are released into the maternal circulation in increasing amounts with advancing gestational age, and this release is further exacerbated with stress. There are good in vitro evidence that STB-EVs are taken up by macrophages and liver cells with additional evidence supporting endothelial cell uptake. STB-EV targeting remains in the early stages of discovery.